2010
DOI: 10.1007/s10637-010-9547-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 2-amino-1-thiazolyl imidazoles as orally active anticancer agents

Abstract: Designed from a high throughput screened hit compound, novel 2-amino-1-thiazolyl imidazoles were synthesized and demonstrated cytotoxicity against human cancer cells. 1-(4-Phenylthiazol-2-yl)-4-(thiophen-2-yl)-1H-imidazol-2-amine (compound 2), a 2-amino-1-thiazolyl imidazole, inhibited tubulin polymerization, interacted with the colchicine-binding sites of tubulins, and caused cell cycle arrest at the G(2)/M phase in human gastric cancer cells. Disruption of the microtubule structure in cancer cells by compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In another work, a group of imidazoles linked with a thiazole moiety were promoted as orally active microtubule destabilizing anticancer agents. 148 The reported imidazoles were evaluated for cytotoxic activity against the human gastric cancer NUGC-3 cells. Among the group, compound 22 (1-(4-phenylthiazol-2-yl)-4-(thiophen-2-yl)-1H-imidazol-2-amine) with an IC 50 value of 0.05 μM was found to be potent against human cancer cells.…”
Section: Imidazoles As Microtubule Destabilizing Anticancer Agentsmentioning
confidence: 99%
“…In another work, a group of imidazoles linked with a thiazole moiety were promoted as orally active microtubule destabilizing anticancer agents. 148 The reported imidazoles were evaluated for cytotoxic activity against the human gastric cancer NUGC-3 cells. Among the group, compound 22 (1-(4-phenylthiazol-2-yl)-4-(thiophen-2-yl)-1H-imidazol-2-amine) with an IC 50 value of 0.05 μM was found to be potent against human cancer cells.…”
Section: Imidazoles As Microtubule Destabilizing Anticancer Agentsmentioning
confidence: 99%
“…Moreover, this compound could distribute efficiently to the tumor tissues at effective concentrations and significantly prolong the lifespan of the leukemia mice. Contrast tests revealed that the replacement of thiophene and phenyl groups by other fragments would decrease the anticancer potency . These amino imidazole‐based tubulin‐targeting compounds are worthy to be further investigated as potential candidates for cancer chemotherapy.…”
Section: Imidazoles As Anticancer Agentsmentioning
confidence: 99%
“…The dacarbazine, an anticancer agent containing imidazole nucleus are used in the treatment of various cancers such as sarcoma, metastatic malignant melanoma, neuroblastoma, islet cell carcinoma, Hodgkin lymphoma, carcinoma of the pancreas and medullary carcinoma of thyroid [35] . Some other examples of marketed drugs used in cancer‐containing imidazole scaffold including nocodazole, bendamustine, veliparib, glasdegib, abemaciclib, liarozole, crenolanib, pracinostat, tipifarnib have been shown in Figure 3 [36] …”
Section: Introductionmentioning
confidence: 99%